Penggunaan dan Pengungkapan Pendapatan Non Halal Pada Perbankan Syariah di Indonesia - Soleha, Soleha; Silvia, Sineba Arli (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Use and disclosure of non-halal income in Islamic banking in Indonesia to analyze the use and disclosure of non-halal income in the financial statements of Islamic banking in Indonesia. The purpose of this study is to find out whether Islamic banking in Indonesia has explained the use and disclosure of non-halal income. The research method used is a qualitative method with a descriptive approach. The data used is a type of secondary data. The secondary data referred to in this study was taken from the annual reports of Islamic Commercial Banks (BUS) in Indonesia for the 2020-2021 period which have been published on the official website of each bank that is a member of Islamic Commercial Banks (BUS). Meanwhile, the reports referred to in this study include non-halal income financial reports, both those that are an integral part of a report and those that stand alone. The population in this study is all Islamic Commercial Banks (BUS) in Indonesia for the 2020-2021 period. The results of the research show that in 2021 only Bank Aladin Syariah does not have non-halal sources of income. Meanwhile, for other banks, namely Bank Panin Dubai Syariah in 2020 and 2021, it does not explain the use and acquisition of non-halal income. Other banks such as Bank Bukopin Syariah, Bank Aceh Syariah, BTPN Syariah, BCA Syariah, BJB Syariah, and BSI have explained the source and use of benevolent funds in their financial reports.